Constitutional Courts and the Implementation of EU Directives: A Comparative Analysis (Polish Yearbook of International Law, 2018)
This article concerns constitutional problems related to the implementation of EU directives seen from both the legal and comparative perspectives. The directives are a source of law which share a number of characteristic features that significantly affect and determine the specificity of Member States’ constitutional review of the directives as well as the legal acts that implement them. The review of the constitutionality of EU directives is carried out in accordance with the provisions of national implementing acts. Member States’ constitutional courts adopt two basic positions in this respect. The first position (adopted by, inter alia, the French Constitutional Council and German Federal Constitutional Court) is based on the assumption of a partial “constitutional immunity” of the act implementing the directive, which results in only a partial control of the constitutionality of the implementing acts, i.e. the acts of national law implementing such directives. The second position, (adopted, explicitly or implicitly by, inter alia, the Austrian Federal Constitutional Court, Czech Constitutional Court, Polish Constitutional Court, Romanian Constitutional Court and Slovak Constitutional Court) concerns the admissibility of a full review of the implementing acts. This leads to the admissibility of an indirect review of the content of the directive if the Court examines the provision as identical in terms of content with an act of EU law. Another issue is related to the application of the EU directives as indirect yardsticks of review. The French Constitutional Council case-law on review of the proper implementation of EU directives represents the canon in this regard. Nonetheless, interesting case studies of further uses of EU directives as indirect yardsticks of review can be found in the case law of other constitutional courts, such as the Belgian Constitutional Court or Spanish Constitutional Court. The research presented in this paper is based on the comparative method. The scope of the analysis covers case law of the constitutional courts of both old and new Member States. It also includes a presentation of recent jurisprudential developments, focusing on the constitutional case-law regarding the Data Retention Directive and the Directive on Combating Terrorism.